2011
DOI: 10.1182/blood-2010-05-283838
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the human platelet sheddome

Abstract: Activated platelets shed surface proteins, potentially modifying platelet function as well as providing a source of bioactive fragments. Previous studies have identified several constituents of the platelet sheddome, but the full extent of shedding is unknown. Here we have taken a global approach, analyzing protein fragments in the supernate of activated platelets using mass spectroscopy and looking for proteins originating from platelet membranes. After removing plasma proteins and microparticles, 1048 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
130
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 46 publications
7
130
0
Order By: Relevance
“…It also fits well with a recent report that identified calpain in the platelet secretome. 17 We also observed that the in vitro incubation of CCL5 with calpain resulted in the modification of CCL5 and the generation of a truncated variant (CCL5 3-21) that was more chemotactic for monocytes than the full-length protein.More than 19 variants of CCL5 are known to exist, 32 and proteases such as dipeptidyl peptidase IV and cathepsin G can generate 3-68 and 4-68 variants of CCL5. 33,34 Although the clinical significance of these variants is unclear, higher plasma levels of CCL5 (3-68) have been reported in patients with type 2 diabetes.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It also fits well with a recent report that identified calpain in the platelet secretome. 17 We also observed that the in vitro incubation of CCL5 with calpain resulted in the modification of CCL5 and the generation of a truncated variant (CCL5 3-21) that was more chemotactic for monocytes than the full-length protein.More than 19 variants of CCL5 are known to exist, 32 and proteases such as dipeptidyl peptidase IV and cathepsin G can generate 3-68 and 4-68 variants of CCL5. 33,34 Although the clinical significance of these variants is unclear, higher plasma levels of CCL5 (3-68) have been reported in patients with type 2 diabetes.…”
mentioning
confidence: 71%
“…It also fits well with a recent report that identified calpain in the platelet secretome. 17 We also observed that the in vitro incubation of CCL5 with calpain resulted in the modification of CCL5 and the generation of a truncated variant (CCL5 3-21) that was more chemotactic for monocytes than the full-length protein.…”
mentioning
confidence: 71%
“…12 Shedding of GPVI in response to ligands is probably mediated by members of the A Disintegrin And Metalloproteinase (ADAM) family of proteases. 17,18 Whether exposure of platelets to elevated shear rates is sufficient to down-regulate GPVI expression and/or increase GPVI shedding has not yet been addressed; however, it may be of clinical relevance in thrombotic diseases where disturbed blood flow is important, for example, in aortic valve stenosis 19 or in patients on coronary bypass. 20 In this regard, elevated surface levels of GPVI on circulating platelets correlate with increased incidence of stroke and acute coronary syndrome, 21 and elevated plasma levels of sGPVI have been reported in a stable angina pectoris (SAP) cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Tryptic peptides originated from abundant proteins predominate, no matter what kind of analysis is performed in the mass spectrometer. Highly abundant proteins such as albumin in blood samples, cytoskeleton proteins in pelleted cells, among other examples, need to be removed to allow detection of less abundant ones, and require separate analyses [7]. The same situation happens in plant derived materials, in which the amount of RuBisCO in leaves and of storage proteins in seeds and seedlings mask the non abundant proteins in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Besides different strategies used to deal with this situation (exclusion lists, dynamic exclusion, affinity columns), it is still challenging and will not be focused in this chapter. For further reading, please refer to selected references cited ahead [7][8][9][10]. The last step is to combine the peptide identification results into a list of proteins that are most likely present in the sample [56,58].…”
Section: Importance Of Sample Preparation For Tandem Mass Spectrometrmentioning
confidence: 99%